Developmental Trajectories of Feeding Problems in Children with Autism Spectrum Disorder. (15th May 2019) - Peverill, Sarah; Smith, Isabel M; Duku, Eric; Szatmari, Peter; Mirenda, Pat; Vaillancourt, Tracy; Volden, Joanne; Zwaigenbaum, Lonnie; Bennett, Teresa; Elsabbagh, Mayada; Georgiades, Stelios; Ungar, Wendy J
Abstract: Objective: Although feeding problems are a common concern in children with autism spectrum disorder (ASD), few longitudinal studies have examined their persistence over time. The purpose of this study was to examine the developmental progression of feeding problems across four time points in preschoolers with ASD. Methods: Group-based trajectory analyses revealed four distinct trajectories of feeding problems in our sample ( N = 396). Results: The majority of children showed levels of feeding problems that were low from the outset and stable (Group 1; 26.3%) or moderate and declining over time (Group 2; 38.9%). A third group (26.5%) showed high levels of feeding problems as preschoolers that declined to the average range by school age. Few participants (8.3%) showed evidence of severe chronic feeding problems. Feeding problems were more highly correlated with general behavior problems than with autism symptom severity. Conclusions: Overall, our findings demonstrated that in our sample of children with ASD, most feeding problems remitted over time, but a small subgroup showed chronic feeding problems into school age. It is important to consider and assess feeding problems in ASD against the backdrop of typical development, as many children with ASD may show improvement with age.